Genomic Analysis of CTX-M-Group-1-Producing Extraintestinal Pathogenic E. coli (ExPEc) from Patients with Urinary Tract Infections (UTI) from Colombia - Elsa De La Cadena; María Fernanda Mojica; Nathaly Castillo; Adriana Correa; Tobias Manuel Appel; Juan Carlos García-Betancur; Christian José Pallares; María Virginia Villegas (MDPI AG, 2020)
Background: The dissemination of the uropathogenic O25b-ST131 Escherichia coli clone constitutes a threat to public health. We aimed to determine the circulation of E. coli strains belonging to O25b:H4-B2-ST131 and the H30-Rx epidemic subclone causing hospital and community-acquired urinary tract infections (UTI) in Colombia. Methods: Twenty-six nonduplicate, CTX-M group-1-producing isolates causing UTI in the hospital and community were selected for this study. Results: Twenty-two E. coli isolates harboring CTX-M-15, one CTX-M-3, and three CTX-M-55 were identified. Multilocus Sequence Typing (MLST) showed a variety of sequence types (STs), among which, ST131, ST405, and ST648 were reported as epidemic clones. All the E. coli ST131 sequences carried CTX-M-15, from which 80% belonged to the O25b:H4-B2 and H30-Rx pandemic subclones and were associated with virulence factors iss, iha, and sat. E. coli isolates (23/26) were resistant to ciprofloxacin and associated with amino acid substitutions in quinolone resistance-determining regions (QRDR). We detected two carbapenem-resistant E. coli isolates, one coproducing CTX-M-15, KPC-2, and NDM-1 while the other presented mutations in ompC. Additionally, one isolate harbored the gene mcr-1. Conclusions: Our study revealed the circulation of the E. coli ST131, O25b:H4-B2-H30-Rx subclone, harboring CTX-M-15, QRDR mutations, and other resistant genes. The association of the H30-Rx subclone with sepsis and rapid dissemination warrants attention from the public health and infections control.